Investigation of dyeing based on pandanus amaryllifolius for superhydrophobic coating in cotton-polyester blended in textile application - Marsi, Noraini; Chew, Gin Yan; Mohd Rus, Anika Zafiah; Kunchi Mon, Siti Zaharah (Penerbit UTHM, 2020)
Natural dyes are derived from natural resources. Colouring materials obtained from natural resources of plant, animal, mineral, and microbial origins were used for colouration of various textile materials. Use of natural dyes started fall after the invention of synthetic dyes in the second half of the nineteenth century. The synthetic dyes were rapidly industrialization of textile production resulted in almost complete replacement of natural dyes by synthetic dyes because their easy availability simple application process, better fastness properties and consistency of shades [1]. Recent environmental awareness has again revived interest in natural dyes mainly among environmentally conscious people. Natural pigments are considered eco-friendly as these are renewable and biodegradable which is skin friendly and provide healthier benefits to the wearer [2]. Pandanus amaryllifolius also called as pandan leaf is a tropical plant that under screw pine genus and it can be easily found all around in Malaysia. It is a genus monocotyledon plants with over 750 accepted species. Extraction of green pigments from pandanus amaryllifolius to produce an organic pigment for fabric dyeing can become an alternative of synthetic pigments. Organic pigments also can be classified as a biochrome substance which is produced by living organisms. These biological pigments include flower and plant pigments [3].